From Struggle to Strength: Women Reformers of Maharashtra Shaping India's Gender Equality Movement - Sarika M. Jagtap; A.K. Patil; Dipali R. Wagh; Sneha C. Kardile; Monika P. Kshirsagar (International Journal of Trends in Humanities, 2026)
The issue of gender equality has been a persistent problem all over the world for a very long time. India has made significant progress in this area, primarily as a result of the efforts made by social reformers and activists. Among them, women from the state of Maharashtra have been the driving force behind the advancement of gender equality. They have frequently challenged the norms of society in order to elevate and empower women. This paper emphasizes the efforts of important women, including Savitribai Phule, Tarabai Shinde, Ramabai Ranade, Pandita Ramabai, Lakshmibai Rajwade, and Chhaya Datar, who campaigned against gender inequality and worked towards women's empowerment. They provided the groundwork for educational reforms, legal changes, and social justice movements in India through their efforts. The suggested paper covers Indian women's struggles and movements from the past to the present. Women currently hold a major position in politics, thanks to women's movements. The women's movement progressed alongside the fight for national liberation. Women's contributions to the independence fight led to constitutional guarantees for equal rights and adult suffrage. However, constitutional provisions have not materially improved the lives of most Indian women in terms of social and material changes. The women's movement originated from patriarchy and gender inequity in society. The women’s movement aims to outlaw patriarchy and gender injustice within and beyond the home. Despite various women's movements, patriarchy persists in India, which is terrible. The purpose of this research is to analyze the causes that led to the formation and emergence of the Indian women's movement. Historical depictions of ‘sati’ and widespread feticides show Indian women's backwardness. India, however, has many 19th- and 20th-century reform movements. Essentially, this history affects present women. This study explores the evolution of the Indian women's movement from pre-independence to post-independence and modern times.
Keywords: Empowerment of women India; Gender equality advocacy; Gender rights and activism; Women and socio-political change